2013
DOI: 10.1074/jbc.m112.418715
|View full text |Cite
|
Sign up to set email alerts
|

The N-terminal 45-kDa Domain of Dna2 Endonuclease/Helicase Targets the Enzyme to Secondary Structure DNA

Abstract: Background:The biochemical function of variable N-terminal regions of eukaryotic Dna2 remains unclear. Results: The N-terminal 45-kDa domain of yeast Dna2 targets the enzyme specifically to a secondary structure flap. Conclusion:The hairpin binding activity of Dna2 contributes to efficient removal of hairpin flaps together with endonuclease and helicase activities during Okazaki fragment processing. Significance: The hairpin binding activity of Dna2 is critical for genome stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 56 publications
(80 reference statements)
4
25
0
Order By: Relevance
“…2B). It was shown that the N-terminal 405-aa deletion is not a loss-of-function mutation in enzymatic activity; the Dna2⌬405N mutant enzyme is catalytically as active or more active than wild type Dna2 under some circumstances (28,31). This observation suggests that the types of DNA damages caused by dna2⌬405N are not critically dependent on the elevated levels of Rad51 or Rad52 for repair.…”
Section: Rad52 Fails To Suppress the N-terminally Deleted Dna2 But Ismentioning
confidence: 66%
See 4 more Smart Citations
“…2B). It was shown that the N-terminal 405-aa deletion is not a loss-of-function mutation in enzymatic activity; the Dna2⌬405N mutant enzyme is catalytically as active or more active than wild type Dna2 under some circumstances (28,31). This observation suggests that the types of DNA damages caused by dna2⌬405N are not critically dependent on the elevated levels of Rad51 or Rad52 for repair.…”
Section: Rad52 Fails To Suppress the N-terminally Deleted Dna2 But Ismentioning
confidence: 66%
“…It was interpreted that the Rad27-n,p allows Okazaki fragments to be processed by other alternative nucleases such as Dna2 or even by the 3Ј to 5Ј exonuclease activity of Pol ␦ (63). Recently, it was shown that Dna2 is involved in the activation of the Mec1 kinase, a sensor protein for the intra-S-phase checkpoint activation (27,28). Therefore, it is possible that Dna2-K1080E in a complex with the 5Ј-structured flap could cause cell death due to the hyperactivation of the intra-S-phase checkpoint.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations